2006
DOI: 10.1021/je0601098
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility Studies of Binary Solutions Involving Water as a Solute in Nonaqueous Solvents at T = 298.15 K

Abstract: The experimental measurements of the speed of sound and density in binary solutions of MeOH, EtOH, n-PrOH, n-BuOH, acetonitrile (ACN), dimethylformamide (DMF), tetrahydrofuran (THF), and 1,4-dioxane as solvents and water as the solute in the concentration range of 0.02 mol·kg-1 to 1 mol·kg-1 at T = 298.15 K are reported. The data are used to obtain the isentropic compressibility of solution. The apparent molar volume (φV) and compressibility (φK) of water at different concentrations are evaluated. The data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…Introduction of a non-polar groups elevates this effect as can be seen in case of PG and TMU, where, there is comparatively more volume loss. Similar comparison with other solvents like DMF, dioxane, THF and acetonitrile (15.1 AE 10 À6 , 17.3 AE 10 À6 , 17.1 AE 10 À6 , and 17.4 AE 10 À6 m 3 AE mol À1 , respectively) [8] indicate the individuality of the solvent structures and the nature of dipolar forces as well as ability to have H-bonding interactions. In case of PC, we observed increase in the molar volume of water which may be attributed to specific H-bonding interaction with the etheric oxygen of the solvent molecules.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Introduction of a non-polar groups elevates this effect as can be seen in case of PG and TMU, where, there is comparatively more volume loss. Similar comparison with other solvents like DMF, dioxane, THF and acetonitrile (15.1 AE 10 À6 , 17.3 AE 10 À6 , 17.1 AE 10 À6 , and 17.4 AE 10 À6 m 3 AE mol À1 , respectively) [8] indicate the individuality of the solvent structures and the nature of dipolar forces as well as ability to have H-bonding interactions. In case of PC, we observed increase in the molar volume of water which may be attributed to specific H-bonding interaction with the etheric oxygen of the solvent molecules.…”
Section: Discussionsupporting
confidence: 64%
“…and water as a solute in the concentration range of 0.1-1 mol AE kg À1 of water at T = 298.15 K [8,9] for solutions having enough solubility or up to the saturation if solubility is limited. Our dielectric studies revealed that water dissolves in benzene may be in cyclic trimer form exhibiting trimer-monomer type of dissociative equilibria [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water dissolved in the aprotic dipolar solvent present a rare opportunity for studying both the state and specific features of solute molecules being hydrogen-non-bonded in the three-dimensional network characteristic of the ''pure" aqueous component and the nature of their effect on the structure and thermodynamic properties of the surrounding (solvating) medium [1][2][3][4][5][6][7]. Here, the point is that the aprotic dipolar solvent is such a dissolving medium, whose structural packing contains molecules that do not form strong hydrogen bonds (due to the absence of proton-donating centers) but allows sufficiently strong specific interactions (via H-bonding) with molecules of an electron-accepting protic solute, which in this case is water [3].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, although thermodynamics does not yield directly the structural aspects of the intermolecular interaction, one can derive meaningful inferences from thermodynamic properties such as partial volume and enthalpy function as well as their derivatives (partial expansibility, compressibility and heat capacity) indirectly [2][3][4]7,8]. From this viewpoint, approaches that cause ''minimal perturbation" of a solution structure seem to be most informative for the specified thermodynamic studies.…”
Section: Introductionmentioning
confidence: 99%